REFORMULASI ETIKA DAKWAH BERBASIS KOMUNIKASI PROFETIK DALAM AL-QUR’AN - Ridho, Abdul Rasyid; Hariyadi, Muhammad (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2021)
Prophetic communication is communication that refers to the prophetic communication pattern of Muhammad Saw. loaded with values ??and ethics. This paradigm is a development of the concept of social prophetic science (ISP) which was initiated by contemporary Islamic scientist, namely Kuntowijoyo. Da'wah as a means of disseminating information through the media in modern times does not always have a positive impact on the purpose of da'wah. In the new era, the media actually gave birth to many provocative da’wah, which caused divisions and contradictions. It is very sad if the da'is and activists do not integrate ethics and prophetic values. So that the impact can cause a lot of hate speech (hatespeech) and lies (hoaxs) to preach. This phenomenon is very inversely proportional to the teachings of peaceful Islam as practiced by the Prophet Muhammad. Therefore, reformulation of prophetic-based da'wah is very urgent in modern times.